(Co)narrações de viagens para Portugal por lusodescendentes no Facebook - Marques, Isabelle Simões (2018)
This article combines the study of online narratives as social practices and the linguistic anthropological study of imagined communities, to examine a set of non-canonical narrative practices in a Facebook group for the Portuguese diaspora in France. Instead of reports of individual members’ past experiences, these narratives function as invitations to other group members to co-tell typical, shared experiences. Specifically, we investigate how group members share vacation trips to Portugal with each otherin ways that produce a sense of collective and simultaneous experience. They accomplish this through deictically-based narrative strategies that shift the social, spatial, and temporal perspectives of narrating and narrated frames in ways that link the following: individual I’s with collective we’s, one-time events with timeless event types, and co-presence on-line with co-presence on vacation. Through these strategies, participants connect Facebook narrations of vacations to the larger social project of diasporic longing for and return to Portugal.